Clinical and Pharmacological Analysis of the Acute Coronary Syndrome Patients Under 45 Years of Age: A Prospective Cohort Study - Nashtar, Saad Badai; Nazzal, Muhammed Mutar; Faeq, Hayder Mohammed; Afroz Abidi (Scripta Medica, 2024)
Background/Aim: Acute coronary syndrome (ACS) in young people is a problem of growing concern. There is an increasing need to evaluate this disease and predict its sequelae for better prevention and management. Aim of this study was to analyse clinical and pharmacological aspects of ACS hospitalised patients for a better evaluation and prediction. Methods: The study included questionnaire based data taken from 225 patients (207 males, 18 females) admitted to Ibn Al-Nafees tertiary cardiac centre. Socio-economic, clinical and pharmacological data were obtained from all patients with follow up from time of admission to discharge. Results: Male to female ratio was 11.5:1, anterior infarction was the predominant site (54.6 %), mortality rate was 1.3 %. Ejection fraction (LVEF) was below 45 % in 66.7 % of the patients, majority (70.7 %) with ischaemic hypokinesia. Smoking was the most common risk factor (77.3 %). Heart failure (HF) was the most common complication (57.3 %). There were significant relationship between HF occurrence and number of risk factors, LVEF, anterior site of ACS and number of echo findings. There were non-significant increase in relative risk of HF with each risk factor, positive troponin and pre-admission pain duration. Prediction tests showed an ascending positive slope of HF risk with number of risk factors, duration of admission and age. Conclusion: There was a high rate of HF occurrence in this study which is mostly attributed to major wall damage due to blockage of the main coronary artery. Analysis demonstrated a good survival rate but high rate of HF occurrence urges for more consideration of guideline-directed management.